Mechanical-characteristic evaluation of excavation unloading rock mass subject to high-temperature conditions - Chen, Xingzhou; Chen, Lili; Ma, Bin; Zhang, Xu; Du, Wei; Wang, Xu; Yang, Chong (Engineering failure analysis, 2021)
•Effect of unloading and temperature on properties of unlined tunnel surrounding rock.•Considering the state of unlined tunnel rock undergoing excavation and then fire.•High temperature tests and reloading tests were performed on unloaded samples.•Tunnel excavation caused different stress release levels. Recently, the frequency of highway tunnel fire has been increasing annually, which necessitates attention toward the stability and safety of surrounding rocks in the unlined tunnels exposed to fires. This study aimed to investigate the influence of the high temperature of excavation unloading on the physical and mechanical properties of unlined tunnel surrounding rock that has been exposed to fire erosion and tunnel ventilation. To this end, granite specimens that had undergone hierarchical unloading tests were selected as the research object, and high temperature and triaxial reloading tests were carried out on unloading-damaged specimens. The variation of mechanical properties and failure characteristics of unloading-damaged specimens with temperature was analyzed, and the differences in their mass, wave velocity, magnetic properties and apparent characteristics under the influence of high temperatures were compared. The results are as follows: (1) The mechanical properties of the unloading-damaged specimens deteriorate obviously under high temperatures, and the greater the temperature, the higher is the reduction in the sample peak strength; there is an obvious nonlinear relationship between them when the unloading-damaged specimens are reloaded after being exposed to a high temperature, and there is a certain threshold for the reduction of mechanical strength of the specimens due to temperature. (2) During triaxial reloading, the pre-peak strain is not related to the confining pressure, but the post-peak strain is closely related to the unloading confining pressure. The higher the temperature, the greater the post-peak accelerated strain. (3) The unloading effect provides a channel for the high temperature to change the physical and mechanical characteristics of the parent rock. The unloading-damaged specimens are gray white at 25 ℃, gray brown at 300 ℃, and reddish brown at 600 ℃. The results show that the wave velocity of the unloading damage specimen decreases slightly at 300 ℃, but significantly at 600 ℃, with an average decrease of 64.73%. (4) The thermal load intensifies the crack evolution, expansion, and structural relaxation of the unloading-damaged specimens, and the unloading magnitude and temperature change the distribution of the dominant fracture surface of the specimens. The confining pressure plays a dominant role in the deformation and failure of the specimens at low temperatures, while thermal load dominates at high temperatures. The research results can provide a theoretical reference for the engineering design of unlined tunnels with surrounding rocks.